Influence of visual aspects and other features on the soundscape assessment of a university external area. Issue 3 (September 2018) - D'Alessandro, Francesco; Evangelisti, Luca; Guattari, Claudia; Grazieschi, Gianluca; Orsini, Federico
EU Environmental Noise Directive recognized the importance of identifying and preserving "quiet areas." Even if the majority of EU member states have not yet defined what is a quiet area, many researchers have started to investigate the topic using the so-called "soundscape" approach. Designing or preserving a "quiet area" in urban settings can be a challenging task. Schools and universities located in urban areas are often surrounded by areas with high traffic and noise pollution that affect the overall and sonic quality of the external spaces, which should represent pleasant areas where students can relax or study. In this study, the assessment of the soundscape and of the overall environment of the external area of the Literature Department of Roma TRE University (Italy) was investigated and discussed by analysing the acoustic, psychoacoustic and perceptual data collected. The results obtained by a summer measurement campaign were compared with the previous winter outcomes. Moreover, it was investigated how natural features, visual aspects and thermal conditions can affect the users' judgment about the overall and the sonic environment; in particular, the Tranquility Rating Prediction Tool was evaluated, both in winter and summer. The measurements campaign revealed that the obtained values are comparable under winter and summer conditions. Due to this, the differences observed in the perception of the sonic and overall environment are ascribable to higher human voice component, more pleasant visual aspects and climate conditions during the summer. This trend was confirmed by tranquility rating values.